Treatment Outcomes of Advanced Cholangiocarcinoma: A Single-Center Experience from India - Vijayaraghavan, Niranjan; MP, Rakesh; KVS, Latha (South Asian Journal of Cancer, 2022)
Background Survival data for patients with advanced cholangiocarcinoma are very sparse in India. We performed this study to find the median overall survival of patients with advanced cholangiocarcinoma and to identify prognostic factors for survival.Methods This is a retrospective study of 30 patients with inoperable and metastatic cholangiocarcinoma treated with cisplatin and gemcitabine chemotherapy. Overall survival was estimated by the Kaplan–Meier method. Univariate and multivariate analyses were performed to determine the impact of age, gender, performance status, carbohydrate antigen (CA) 19.9, liver function test on survival. Data were analyzed using SPSS version 21.Results The mean age of the population was 47.5 years (±14.5). The most common presenting complaint was jaundice followed by abdominal pain. Extrahepatic cholangiocarcinoma comprised of 86%. Median number of cycles was 4 and the response rate was 46.6% (partial response and stable disease) The median overall survival was 9 months (95% confidence interval = 6.0–11.8 months). The median survival of patients with Eastern Cooperative Oncology Group performance score < 2 and ≥2 were 15.6 and 4.2 months (p = 0.002), respectively. The median overall survival for patients with albumin > 3.0 g/dL was 12.1 and 4.5 months for < 3.0 g/dL (p = 0.039). Patients with CA 19.9 < 200 U/mL had a better overall survival (13.2 months) than those above 200 U/mL (5.6 months) (p = 0.001). In the multivariate analysis, performance status was found to be the only independent prognostic factor.Conclusion Advanced cholangiocarcinoma has a poor prognosis. Performance status, serum albumin, and CA 19.9 were found to be prognostic.
Keywords: cholangiocarcinoma; chemotherapy; survival